Four element triangular dielectric resonator antenna for wireless application. Issue 1 (20th May 2015) - Gangwar, Ravi Kumar; Ranjan, Pinku; Aigal, Abhishek
Abstract : A wideband four element triangular dielectric resonator antenna (TDRA) has been designed and fabricated by using 50 Ω coaxial probe feed. The input and radiation characteristics of the proposed antenna have been extracted through Ansoft HFSS and CST Microwave Studio simulation software and compared with the experimental results. The simulated results have been in good agreement with the experimental results. The proposed antenna characteristics have also been compared with the same dimensions of the single element TDRA, and found enhancement in bandwidth with lower resonant frequency. Its performance has also been compared with same area (equal to proposed antenna) of single element TDRA. The proposed antenna provides nearly 37% bandwidth (|S11 | < −10 dB) at a resonant frequency of 5.45 GHz with 4.76 dBi peak gain. The symmetry and uniformity in the radiation patterns is obtained consistently for the entire operating bandwidth. The proposed antenna shows consistently symmetric monopole type radiation pattern with low cross polarization for WLAN (IEEE 802.16) and WiMAX applications. The performance of the proposed antenna has been compared with some similar type of dielectric resonator antenna (DRA) shapes and it has been observed that TDRA is taking very less radiation area for giving better performance than other DRA shapes.